Activation of extracellular signal-regulated kinase, ERK2, by p21ras oncoprotein. - Leevers, S J (1992)
To examine signal transduction events activated by oncogenic p21ras, we have studied kinases that are activated following the scrape loading of p21ras into quiescent cells. We observe rapid activation of 42 kDa and 46 kDa protein kinases. The 42 kDa kinase is the mitogen and extracellular-signal regulated kinase ERK2, (MAP2 kinase), which is activated by phosphorylation on tyrosine and threonine in response to oncogenic p21ras, while the 46 kDa kinase is likely to be another member of the ERK family. Stimulation of these kinases by oncogenic p21ras does not require the presence of growth factors, showing that oncogenic p21ras uncouples kinase activation from external signals. In ras transformed cell lines, these kinases are constitutively activated. We propose that the kinases are important components of the signal transduction pathway activated by p21ras oncoprotein.